A case for measuring negative willingness to pay for consumer goods. (October 2021) - Bass, Daniel A.; McFadden, Brandon R.; Messer, Kent D.
Highlights: We find that consumers can negatively value products like tap and bottled water. Ignoring negatively values may not reflect consumer sentiments or concerns. Allowing negative values may improve decisions that rely on welfare measures. Abstract: Negative willingness to pay (WTP) has received significant attention in the environmental economics literature but generally has been ignored by economists interested in measuring consumer preferences for food and beverages. Most consumer preference studies have focused solely on WTP measures and, in most cases, have treated negative consumer responses to a product as equivalent to consumers simply not wanting to purchase it since both sentiments have a WTP estimate of 0. However, for some goods such as bottled water, this approach can be an oversimplification that fails to reveal consumers' true sentiments, a problem that is relevant in policy contexts. To test this question, we conduct a randomized controlled study involving 1384 adult consumers that tests how three unconventional elicitation approaches affect estimates of consumer preferences for nearly identical goods: bottled water and tap water. We find that stated values for both types of water differ by treatment and that ignoring negative WTP values upwardly biases the premium consumers are willing to pay for bottled water. Our findings show that allowing negative values of WTP provides more-accurate valuations and measures of differences in valuations for two goods, something that is particularly important for policymaking since consumer valuations can reflect their support for efforts to address externalities associated with consumer goods or may reflect other consumer sentiments, such as food safety concerns.